Bioaccumulation of trace metals in the coastal Borneo (Malaysia) and health risk assessment. (August 2019) - Anandkumar, A.; Nagarajan, R.; Prabakaran, K.; Bing, Chua Han; Rajaram, R.; Li, Jian; Du, Daolin
Abstract: The concentration of nine trace elements were analyzed in the different tissue organs of commonly available crabs ( Portunus sanguinolentus, Portunus pelagicus and Scylla serrate ) and bivalve ( Polymesoda erosa ) species collected from the Miri coast, Borneo in order to evaluate the potential health risk by consumption of these aquatic organisms. Among the analyzed organs, metal accumulation was higher in the gill tissues. The essential (Cu and Zn) and non-essential (Pb and Cd) elements showed the highest (i.e. Zn) and lowest concentrations (i.e. Cd) in their tissue organs, respectively. The estimated daily intake and hazard indices of all metals in the muscle indicate that the measured values were below the provisional tolerable daily intake suggested by the joint FAO/WHO Expert Committee on Food Additives. Compared to Malaysian and international seafood guideline values the results obtained from the present study are lower than the permissible limits and safe for consumption. Graphical abstract: Unlabelled Image Highlights: Concentrations of nine trace elements (Cu, Cd, Co, Cr, Mn, Ni, Pb, Rb and Zn) were analyzed in three crabs and a bivalve species. Female crabs show higher accumulation than male. Maximum concentration of metals was observed in gill tissues and minimum concentration was observed in muscle tissues. Based on estimated daily intake and hazard indices, none of the metals will pose any adverse health effects to humans. Essential elements (Cu & Zn) were accumulated at a higher efficiency than non-essential elements (Cd & Pb).